Chemical admixtures — Chemistry, applications and their impact on concrete microstructure and durability. (December 2015) - Plank, J.; Sakai, E.; Miao, C.W.; Yu, C.; Hong, J.X.
Abstract: An overview of current PCE compositions and synthesis methods is provided, followed by novel applications for PCEs including C–S–H-PCE nano-composites and a description of still unresolved challenges for PCE technology. In addition, the functionality of chemical admixtures in specific applications for low-carbon cements and concrete systems is discussed. The action mechanisms of retarders and the recycling system of sludge water by using retarder are introduced. Furthermore, the influence of fluoride ion and the effectiveness of PCE polymers in blended cements and the effect of non-adsorbed polymer are presented. And the impact of special interface modifying materials, of a refined pore structure and of chemical admixtures, particularly shrinkage-reducing agents, is described. The article concludes that more accurate quantitative micro-analytical methods and modeling tools will be needed to obtain a holistic understanding of factors affecting the microstructure of concrete, with the final goal of achieving a more durable concrete.